Overdiagnosis: An Understudied Issue in Hepatocellular Carcinoma Surveillance - Rich, Nicole E.; Parikh, Neehar D.; Singal, Amit G. (Seminars in Liver Disease, 2017)
Overdiagnosis, the detection of clinically insignificant disease that would not otherwise impact the patient's lifespan, is a phenomenon that has been described in several solid tumors, such as prostate, breast, thyroid, and lung cancers. Population-based efforts to reduce hepatocellular carcinoma (HCC) mortality in cirrhosis patients by screening and early detection may result in the overdiagnosis of HCC. One of the harms of overdiagnosis is subsequent overtreatment, which can result in increased costs, as well as physical side effects, psychological harms, and poorer quality of life. In this review, the authors explore the potential for overdiagnosis in HCC.
Keywords: overdiagnosis; overtreatment; harms; surveillance; screening; HCC